The methyl jasmonate-responsive transcription factor DobHLH4 promotes DoTPS10, which is involved in linalool biosynthesis in Dendrobium officinale during floral development. (August 2021) - Yu, Zhenming; Zhang, Guihua; Teixeira da Silva, Jaime A.; Zhao, Conghui; Duan, Jun
Highlights: Terpene synthase DoTPS10 is responsible for linalool biosynthesis in D. officinale . Expression patterns of DobHLH4 correlate with DoTPS10 during floral development. DobHLH4 binds to the DoTPS10 promoter and increases its transcriptional activity. Nucleus-localized DobHLH4 is modulated by MeJA, and interacts with DoJAZ1. Overexpression of DobHLH4 evidently increases linalool production in D. officinale . Abstract: Linalool is an aromatic monoterpene produced in the Chinese medicinal plant Dendrobium officinale, but little information is available on the regulation of linalool biosynthesis. Here, a novel basic helix-loop-helix (bHLH) transcription factor, DobHLH4 from D. officinale, was identified and functionally characterized. The expression profile of DobHLH4 was positively correlated with that of DoTPS10 ( R 2 = 0.985, p < 0.01), which encodes linalool synthase that is responsible for linalool production, during floral development. DobHLH4 was highly expressed in petals, and was significantly induced by methyl jasmonate. Analysis of subcellular localization showed that DobHLH4 was located in the nucleus. Yeast one-hybrid and dual-luciferase assays indicated that DobHLH4 bound directly to the DoTPS10 promoter harboring the G-box element, and up-regulated DoTPS10 expression. A yeast two-hybrid screen confirmed that DobHLH4 physically interacted with DoJAZ1, suggesting that DobHLH4 might function in the jasmonic acid-mediated accumulation of linalool. Furthermore, transient overexpression of DobHLH4 in D. officinale petals significantly increased linalool production by triggering linalool biosynthetic pathway genes, especially DoTPS10 . We suggest a hypothetical model that depicts how jasmonic acid signaling may regulate DoTPS10 by interacting with DobHLH4 and DoJAZ1. In doing so, the formation of linalool is controlled. Our results indicate that DobHLH4 is a positive regulator of linalool biosynthesis and may be a promising target for in vitro -based metabolic engineering to produce linalool.